Optimal regulatory design for the Central Bank of Russia - Sophie Claeys (Bank of Finland, Institute for Economies in Transition (BOFIT), 2005)
The Central Bank of Russia (CBR) assumes a wide range of functions not raditional to a central bank.In addition to the daily conduct of monetary policy, it acts as a regulator and supervisor of the banking sector.It is currently overssing the implementation of a deposit insurance scheme and is the main owner of Russia's largest commercial bank, Sberbank.As this additional functions may conflict with the CBR policy objectives, I review how the current design of the CBR deviates from the optimal allocation of regulatory powers within a central bank prescribed in the literature.I then empirically investigate the need for a supervisory body within the CBR.Using a simple Taylor rule framework I find that the CBR does not use its "hands-on" supervisory information to maintain financial stability, but rather to accomodate state-owned banks' balances.
URN:NBN:fi:bof-201408072143
Keywords: G21; G28; 330; Central Bank; Prudential Regulation and Supervision; Monetary Policy Rules; Russia